Efektivitas Media Pop-Up Book dalam Menstimulasi Literasi Numerasi Anak Usia 5-6 Tahun - Rosmawati, Rosmawati; Aryani, Nini; Herwina, Herwina (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
Low numeracy literacy skills in early childhood, such as difficulty recognizing number symbols and quantity concepts, pose a challenge in preparing for primary education. This study aims to improve the numeracy literacy skills of children aged 5–6 years through the use of Pop-Up Book media. The research method employed was Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles. The subjects were 19 children at KB Kasih Bunda, Indragiri Hilir. Data were collected through observation sheets, documentation, and interviews, then analyzed using descriptive comparative analysis. The results showed a significant increase in each cycle. In the pre-cycle stage, children's average ability ranged from 30%–45%. After the implementation of Pop-Up Book media, the scores increased to 50%–68% in Cycle I and peaked at 80%–90% in Cycle II. Beyond cognitive aspects, children's learning enthusiasm also increased to 85%. It is concluded that Pop-Up Book media is effective in improving early childhood numeracy literacy by providing interactive and concrete visualizations. This media is recommended as an innovative learning tool to support holistic cognitive development in children.